Production of artemisinin in shoot cultures of Artemisia cina irradiated callus - Aryanti Aryanti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Artemisinin is an antimalaria agent that is only found in Artemisia sp. medicinal plant. This compound is occurred at very low level in that plant. Irradiated callus of Artemisia cina have been conducted by the dose of 40 Gy to improve artemisinin content in shoot cultures. Regeneration of irradiated callus to shoot cultures formation has been successful in Murashige & Skoog (MS) medium combined with Naphtalene Acetic Acid (NAA) 1 mg/g, Benzyl Amino Purin (BAP) 2 mg/L and 15 % coconut water. Ten mutant lines of shoot cultures have been analyzed for the artemisinin content. The artemisinin content of mutant lines were higher than the original plant. The highest artemisinin content is 5 mg/g found in mutant line number 404, this line also has wider leaf area than original plant.Key word : artemisinin, Artemisia cina, shoot cultures, irradiated callus